2022
DOI: 10.1364/ao.457148
|View full text |Cite
|
Sign up to set email alerts
|

Scanning force sensing at micrometer distances from a conductive surface with nanospheres in an optical lattice

Abstract: The center-of-mass motion of optically trapped dielectric nanoparticles in a vacuum is extremely well decoupled from its environment, making a powerful tool for measurements of feeble subattonewton forces. We demonstrate a method to trap and maneuver nanoparticles in an optical standing wave potential formed by retroreflecting a laser beam from a metallic mirror surface. We can reliably position a ∼ 170 n m diameter silica nanoparticle at distances of a few hundred nanom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This corresponds to a linear velocity of 1.4 km s –1 between the tip of the nanodumbbell and the sapphire surface, separated by 430 nm. While a nanosphere has been levitated near a surface before, ,, to the best of our knowledge, this is the first report on optical levitation and GHz rotation of a nonspherical nanoparticle near a surface. Such a levitated GHz nanorotor near a surface can be used to explore fundamental physics, including measuring quantum friction. , …”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This corresponds to a linear velocity of 1.4 km s –1 between the tip of the nanodumbbell and the sapphire surface, separated by 430 nm. While a nanosphere has been levitated near a surface before, ,, to the best of our knowledge, this is the first report on optical levitation and GHz rotation of a nonspherical nanoparticle near a surface. Such a levitated GHz nanorotor near a surface can be used to explore fundamental physics, including measuring quantum friction. , …”
mentioning
confidence: 90%
“…Recently, quantum ground state cooling of the center-of-mass (CoM) motion of an optically levitated nanosphere in a vacuum was achieved, , showing the great potential of levitated nanoparticles for studying macroscopic quantum mechanics . Meanwhile, levitated dielectric particles in vacuum are ultrasensitive force detectors, and their CoM motion has been proposed to detect short-range forces, dark matter, dark energy, high-frequency gravitational waves, and quantum gravity . Besides the CoM motion, there is increasing interest in the torsional and rotational motions of nonspherical particles. Levitated nonspherical nanoparticles in free space have been driven to rotate at GHz frequencies , and cooled by active feedback, , coherent scattering, and spin-optomechanical interaction .…”
mentioning
confidence: 99%
“…The field of levitated optomechanics is both rapidly developing and of high scientific interest, with a number of impressive recent results including achieving cooling to the quantum ground state [1,2], high resolution surface force mapping [3][4][5], material limited GHz rotations [6], microscopic material studies [7], and high precision force [8] and acceleration [9] sensitivity. Near term goals include contributions to dark matter and energy searches [10] and astrophysics, including searches for high frequency gravitational waves (GWs) in the Leviated Sensor Detector (LSD), currently under construction [11].…”
mentioning
confidence: 99%
“…This shaking releases nano particles that can be trapped. Piezo launching has been widely used to trap particles ranging from 170nm to 3µm in diameter [110][111][112] as well as clumps of particles [113]. It Chapter 5 Shaun J. Laing has been demonstrated that this method works in vacuum down to pressures of 0.6mbar.…”
Section: A Single Source Talbot Interferometermentioning
confidence: 99%